Personal Data Protection Violations By Fintech Lending in Indonesia - Nurul Insi Syahruddin; Eva Achjani Zulfa (Dinasti Research, 2024)
The development of increasingly modern technology has changed the pattern of human behavior and work methods, which were initially conventional and then digitalized, one of which is marked by the presence of financial technology (fintech) lending. The rise of fintech lending development also has a negative impact, one of which is in terms of processing the personal data of fintech lending users. Hence, the Financial Services Authority formed POJK 10/2022. In connection with this, the PDP Law has also come into force in Indonesia. This paper aims to look at personal data protection violations by fintech lending, considering that two institutions have the authority to handle these violations. The method used is doctrinal legal research. The approach used is the statute approach. The results showed that to supervise fintech lending, it is necessary to classify its position first. If fintech lending is an LPBBTI organizer, it is supervised by OJK. Meanwhile, if fintech lending is the controller of personal data, it is supervised by the PDP Authority. As for reports or complaints of allegations and/or violations of personal data protection committed by fintech lending; examination and investigation of complaints of alleged violations of personal data protection; and imposition of administrative sanctions for violations of personal data protection by fintech lending are the authority of the PDP Authority, not OJK.